2012
DOI: 10.1115/1.4006902
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Estimation Methods of Strain Range in Notched Specimens Made of Mod.9Cr-1Mo Steel

Abstract: Several methods of estimating strain range at a structural discontinuity have been developed in order to assess component reliability. In a component design at elevated temperature, estimation of strain range is required to evaluate the fatigue and creep-fatigue damage. Therefore, estimation of strain range is one of the most important issues when evaluating the integrity of a component during its lifetimes. To verify the methods of estimating strain range for discontinuous structures, low cycle fatigue tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Experimental results of Refs. [83][84][85] have displayed that the notch presents a strengthening effect and the strengthening effect is more remarkable with the increasing elastic stress concentration factor (see Fig. 13).…”
Section: Strain-controlled Modementioning
confidence: 94%
See 1 more Smart Citation
“…Experimental results of Refs. [83][84][85] have displayed that the notch presents a strengthening effect and the strengthening effect is more remarkable with the increasing elastic stress concentration factor (see Fig. 13).…”
Section: Strain-controlled Modementioning
confidence: 94%
“…For notched bar specimens, strain-controlled creep-fatigue experimental studies on the notched bar components are reported [71,[81][82][83][84][85][86]. For stress-controlled mode mentioned above, the uniform stress at the notch plane is kept as the same as that of the smooth specimens.…”
Section: Strain-controlled Modementioning
confidence: 99%